Investigation of the secondary metabolome of fungi from svalbard islands (chemistry of psychrophilic fungi) / Nur Aisyah Zanal Abidin - Zanal Abidin, Nur Aisyah (2014)
Psychrophilic fungi are believed to produce secondary metabolites. Secondary metabolites such as mycotoxins have an important ecological function. The main objectives of the study is to gain HPLC profiling of the extracts produced by 8 strains of psychrophilic fungi. They were grown in 96-well microtiter plate (MTP). All strains grew well and the extracts were analyzed by High Performance Liquid Chromatography (HPLC). Further study needs to be done to identify the metabolites and compounds of interest for these fungi.